Influencia de la arborización en sistemas de pastoreo racional flexible sobre el estrés calórico en vacas mestizas - Muñoz García, José Patricio (2023)
The present work was carried out with the purpose of measuring the influence of arborization in flexible rational grazing systems on heat stress in crossbred dairy cows in two grazing areas of the pasture and forage unit of the Escuela Superior Politécnica Agropecuaria de Manabí, there were units with a density of 25 trees/ha (T1) and another of 30 trees/ha (T2) and an area as a control treatment without trees (T0), using five repetitions for the three treatments, counting one cow per repetition. giving a total of 15 experimental units, evaluating as a response variable: rectal temperature (TR), heart rate (HR) and respiratory rate (RR) at noon, the moment of maximum heat stress in the tropics. The results obtained in the measurement of rectal temperature, heart rate and respiratory rate of bovines reflect a p-value of <0.001 which testifies that there is a highly significant difference between the treatments, by means of the Tukey test it was observed that the (T0) presented an increase in physiological stress markers, compared to (T1) and (T2), with respect to the temperature humidity index (ITM), the area without access to shade (SOL) showed a difference of 3.84 compared to to the shaded access area (SOM). With the data obtained, it is concluded that the combination of adequate levels of arborization with elements of rational grazing improves the response of physiological markers to heat stress of crossbred cattle in the Ecuadorian dry tropics.